2021
DOI: 10.1093/ejcts/ezab131
|View full text |Cite
|
Sign up to set email alerts
|

Suture tie-down forces and cyclic contractile forces after an undersized tricuspid annuloplasty using a 3-dimensional rigid ring in an ovine model

Abstract: OBJECTIVES This study was conducted to measure suture tie-down forces and evaluate cyclic contractile forces (CCFs) in beating hearts after undersized 3-dimensional (3D) rigid-ring tricuspid valve annuloplasty (TAP). METHODS Eight force transducers were attached to the 3D rigid TAP ring. Segments 1 to 8 were attached from the mid-septal to anterior-septal commissural area in a counterclockwise order. Two-sizes-down ring TAPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
3
2
Order By: Relevance
“…Contrary to a previous study showing significantly higher CCFs in the septal annular area [0.34 (SD: 0.22) N at RVP of 70 mmHg] after TAP using a 3D rigid ring, CCFs in the flexible septal band of the 3D hybrid band remained low [0.19 (SD: 0.14) N at RVP of 70 mmHg]. As in a previous study [ 14 ], the CCFs were the lowest in the posterior annular area. However, unlike the previous study, CCFs of the septal annular area were not statistically different from those of other areas, and there was no tendency of increasing CCFs towards the anterior end of the ring, indicating the favourable effect of the hybrid band in the septal and anterior parts (Fig.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Contrary to a previous study showing significantly higher CCFs in the septal annular area [0.34 (SD: 0.22) N at RVP of 70 mmHg] after TAP using a 3D rigid ring, CCFs in the flexible septal band of the 3D hybrid band remained low [0.19 (SD: 0.14) N at RVP of 70 mmHg]. As in a previous study [ 14 ], the CCFs were the lowest in the posterior annular area. However, unlike the previous study, CCFs of the septal annular area were not statistically different from those of other areas, and there was no tendency of increasing CCFs towards the anterior end of the ring, indicating the favourable effect of the hybrid band in the septal and anterior parts (Fig.…”
Section: Discussioncontrasting
confidence: 94%
“…In the present study, downsized ring annuloplasty was performed using a hybrid band with a wide open anteroseptal aspect to reduce the risk of potential conduction problems, flexible ends for preserving annular movement and a semi-rigid mid-portion for stabilizing the right ventricular (RV) free wall annular aspect [ 10 , 15 ]. The average suture tie-down force of 4.42 (SD: 2.32) N was not lower than the value reported by a previous study using a 3D rigid ring [ 14 ]. This might be expected because the flexible band might have no effect on lowering the suture tie-down forces.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…9 Lim et al reported that the septal leaflet area had higher suture tie-down force loads when performing annuloplasty in an ovine model. 15 An annuloplasty technique considering the lack of fibrous structure and fragility is necessary for successful restrictive annuloplasty with a small size ring. We performed a continuous wrapping suture annuloplasty technique using a flexible total ring, which might be less affected by the number of leaflets and fragility of the annulus structure.…”
Section: Discussionmentioning
confidence: 99%
“…9 Lim et al reported that the septal leaflet area had higher suture tie-down force loads when performing annuloplasty in an ovine model. 15…”
Section: Discussionmentioning
confidence: 99%